Antisaccadic Eye Movements Are Correlated with Corpus Callosum White Matter Mean Diffusivity, Stroop Performance, and Symptom Burden in Mild Traumatic Brain Injury and Concussion - Ting, Windsor Kwan-Chun; Schweizer, Tom A.; Topolovec-Vranic, Jane; Cusimano, Michael D. (Frontiers in Neurology, 2016)
Antisaccades are thought to involve higher level inputs from neural centers involved in rapid eye movement inhibition and control. Previous work has demonstrated that performance on the antisaccade task can help in assessment of injury in acute and/or chronic mild traumatic brain injury (mTBI). In this exploratory study we performed cross-sectional and longitudinal comparisons of rapid eye movement, followed by correlations of antisaccade performance with assessments of symptom burden, diffusion tensor imaging, and a neuropsychological test of response inhibition. Significant deficits in antisaccade median latency, F(2, 31) = 3.65, p = 0.04 and prosaccade error mean duration, F(2, 31) = 3.63, p = 0.04 were found between patient groups and controls: the former was correlated with loss of white matter integrity in the splenium of the corpus callosum in acute mTBI, rho (8) = 0.90, p = 0.0005. Furthermore, increased antisaccade median latency was also correlated with poor performance on an executive functioning task, r2 = 0.439, p = 0.03, and greater symptom burden, r2 = 0.480, p = 0.02 in the acute mTBI patients. Our preliminary research suggests that the antisaccade task could be useful as a neurological marker for mTBI and concussion but more work is required.